PERANAN KEPEMIMPINAN CAMAT DALAM MENINGKATKAN KINERJA SUMBER DAYA MANUSIA DI KANTOR KECAMATAN MEDAN KOTA - Panggabean, Elfrida; Pasaribu, Jhonson; Degedona, L. Primawati (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
This study aims to determine the role of the Camat's leadership in improving the performance of human resources at the Medan City sub- district office. The type of research used is descriptive qualitative. With data collection techniques observation, interviews and documentation to retrieve data in the form of writing, behavior, events, and words. Informants in this study were the Head of Medan City as a key informant, employees as the main informant, and the community as additional informants. From the results of research conducted by researchers, it shows that the Camat at the Medan City District Office carries out his role as a leader, always empowers his staff or employees through collaboration, and involves his staff or employees in decision making. And also always provide direction and supervision to every employee in the Medan City District Office. By providing socialization to all employees in determining the priority of employee performance, direction and supervision are always carried out on their performance, but in this case not all fields that carry out their main duties and functions have not carried out in accordance with the Standard Operating Procedures given by the Camat